Eclampsia: Still a major problem in rural KwaZuluNatal Province South Africa - J Moodley; V Makhanya; L Govender (South African Medical Association, 2016)
Background. Eclampsia is a major direct cause of maternal mortality in South Africa (SA). Most cases of morbidity and mortality areprobably due to late booking for antenatal care, poor quality of care and poor interfacility transport. Publications on eclampsia in SA aremainly from tertiary hospitals and often do not provide clinical management details at the referring hospital.Objective. To describe the obstetric outcomes of eclampsia in a rural area of KwaZulu-Natal (KZN) Province.Methods. This was a chart review of cases of eclampsia admitted to a regional health facility serving 19 maternity clinics and 17 districthospitals in northern KZN.Results. There were 58 cases of eclampsia with complete data during the 6-month study period. Forty-nine women had booked forantenatal care, of whom 11 (22.4%) had risk factors including persistent proteinuria and haematuria. Of the 11, 2 (18.1%) had gestationalhypertension well controlled on methyldopa and managed on an outpatient basis, and 2 with mild to moderate pre-eclampsia on twodifferent types of antihypertensive agents were being treated as outpatients; 3 (27.2%) of these had uncontrolled blood pressure levels ontwo repeated antenatal visits.Conclusion. This clinical audit indicates that a number of cases of eclampsia could have been avoided if clinical protocols had beenfollowed and timeous delivery and/or referrals had been considered.